Tinjauan Fiqh Siyasah Terhadap Putusan Pengadilan Tata Usaha Negara Medan Nomor : 96/G/2023/PTUN.MDN tentang Pembatalan Serta Pemberhentian Pejabat Pimpinan Tinggi Pratama di Lingkungan Pemerintah Provinsi Sumatera Utara - Hafif Pasaribu, Kurniawan; Khalid, Khalid (UNES Law Review, 2024)
This study examines the decision of the Medan State Administrative Court (PTUN) Number 96/G/2023/PTUN.MDN regarding the cancellation of the North Sumatra Governor's decision on the dismissal of high-ranking officials. Using a qualitative method with a descriptive-analytical (normative-juridical) approach, this research aims to analyze the judges' considerations and review the decision from the perspective of Fiqh Siyasah (Qadha’iyyah). The results show that the Medan PTUN annulled the Governor's decision as it was deemed to violate the principles of good governance. From the viewpoint of Fiqh Siyasah, this decision aligns with the principles of justice (al-'adl), legal certainty (al-yaqin), and public interest (maslahah) in Islamic governmental administration. This study concludes the importance of applying Fiqh Siyasah principles in administrative decision-making to ensure justice and public benefit.